The prevalence of Rhizoctonia sp. and its impacts on growth and yields of upland paddy (Oryza sativa) planted under sengon (Paraserianthes falcataria) agroforestry - MUHAMMAD ALAM FIRMANSYAH; ADISTI PERMATASARI PUTRI HARTOYO; NURHENI WIJAYANTO; ERFIANI ERFIANI; ANURAGA JAYANEGARA; TEGUH JATI PURNAMA (Society for Indonesian Biodiversity, 2025)
Abstract. Firmansyah MA, Hartoyo APP, Wijayanto N, Erfiani, Jayanegara A, Purnama TJ. 2025. The prevalence of Rhizoctonia sp. and its impacts on growth and yields of upland paddy (Oryza sativa) planted under sengon (Paraserianthes falcataria) agroforestry. Biodiversitas 26: 2746-2753. Agroforestry is a land management system that integrates trees and agricultural crops to optimize land use for generating socio-economic and ecosystem functions. Sengon (Paraserianthes falcataria), a fast-growing species, can be effectively combined with upland paddy (Oryza sativa) under agroforestry system to enhance land productivity and environmental sustainability, but this system is not free from pests and diseases. This study aimed to analyze the prevalence of disease caused by Rhizoctonia sp. on upland paddy and its impacts on the paddy growth and yields as well as the total biomass of sengon in an agroforestry system. The research employed a completely randomized factorial design with repeated measurements, consisting of two factors: Planting system (monoculture and agroforestry) and paddy varieties (Situpatenggang and IR64); each treatment with three replications. The findings indicated that paddy growth was broadly similar across all treatments, though the disease attack and intensity levels were pervasive and nearly uniform. The agroforestry system, particularly with a planting distance of 2 × 2 meters, increased 23.2% paddy grain weight, although it did not prevent the spread of the inoculated disease. The total sengon biomass was 16.95 Mg/ha, with a total carbon stock of 7.80 MgC/ha, highlighting the potential of agroforestry systems for carbon sequestration. These results suggest that agroforestry systems offer significant benefits for paddy yield and carbon stock; yet they require careful management of disease risks to optimize outcomes. Therefore, integrating sengon and paddy in agroforestry systems positively impacts paddy yields and contributes to environmental sustainability. These findings underscore the importance of agroforestry systems in balancing agricultural productivity with ecological sustainability despite the challenges posed by disease and shading.